(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
The Science, Technology, and Culture Week of IFPB - Catolé do Rocha (SECITEC.CR) is an annual event that takes place at the Federal Institute of Education, Science, and Technology of Paraíba - Catolé do Rocha Campus. In its seventh edition, held in December 2022, the event had the overall theme of "Bicentennial of Independence: 200 years of Science, Technology, and Innovation in Brazil." The following activities took place during the event: opening panel, scientific work exhibition, artistic and cultural showcase, workshops and mini-courses circuit, Hispanic diversity festival, and a scavenger hunt. SECITEC.CR involved faculty, students, staff, and partners from IFPB-CR, including the State University of Paraíba, guest speakers, workshop facilitators, external evaluators, and former students. The students showed great engagement, particularly in the cultural and sports activities. The scientific work exhibition encouraged active and meaningful learning through scientific techniques and methods, preparing the students for external scientific events. The workshops and mini-courses circuit provided the students with access to knowledge beyond the curriculum.